Augmentation of passive magnetic bearing performance by using air or iron intervals. Issue 2 (1st March 2019) - Safaeian, Reza; Heydari, Hossein
Abstract : Purpose: This paper aims to suggest the use of air or iron intervals between axially magnetized rings to increase the forces and stiffness of permanent magnet passive magnetic bearings (PMBs). The paper calculates the stiffness of such bearings through an analytical method and optimizes the dimensions of the magnets for achieving maximum stiffness. Design/methodology/approach: For determining the magnetic fields distribution, forces and stiffness of the bearings, a 2D analytical method is used, based on the subdomain method. For the sake of generalization, all of the parameters are normalized and optimized for maximum normalized stiffness per magnet volume ratio. Findings: The optimum sizes of the magnets as well as the optimum dimensions of the air or iron intervals are calculated in this paper. The optimum sizes of the magnets are around the air gap length and it is very difficult to realize them. Using iron intervals can improve the stiffness to the extremely high values in practical dimensions of the magnets. Originality/value: This paper presents a novel configuration for improving the performance of PMBs with alternately axially magnetized rings.